Landscape impact assessment in planning processes - Gazzola, Paola (De Gruyter, 2019)
The book is specifically dedicated to a broad spectrum of aspects of landscape impact assessment in the process of strategic planning and decision-making. It aims to show the required standard process, content and scope of assessment of impact on the landscape and to present the main principles to ensure their integrity and consistency.